Dampak Aktivitas Wisata terhadap Kelestarian Lingkungan dan Budaya Suku Tengger di Desa Ngadas - Ilyas Azhari; Jihan Atsilah Syahbani; Siti Rohiyatul Jannah (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2025)
This study aims to examine the impact of tourism activities on environmental sustainability and the culture of the Tengger tribe in Ngadas Village, Poncokusumo District, Malang Regency. Ngadas Village is one of the traditional villages located in the Bromo Tengger Semeru National Park area and is a growing natural and cultural tourist destination. The research method used is a qualitative approach with data collection techniques through observation, in-depth interviews, and documentation studies. The results of the study show that tourism activities have a positive impact in the form of economic improvement for the community and the preservation of several cultural traditions through tourist attractions. However, there are also negative impacts such as environmental degradation due to increased waste volume and land use change, as well as the commercialization of culture, which has the potential to diminish the sacred meaning of the Tengger tribe's traditions. This study recommends the need for sustainable and participatory tourism management, involving the indigenous community in decision-making so that environmental and cultural sustainability is maintained amid the development of the tourism sector.